The False Allure of Security Technologies - Casella, Ronnie (Social justice, 2003)
Part of a special section on the intersection of ideologies of violence. An examination of whether the extensive and ever-increasing use of security technology is a sensible reaction to safety problems in society, or whether it is based on totalitarianism and illogical fear, is presented. It is concluded that although the use of security technology is a logical response to unprecedented violence in U.S. society, the reasons behind the security buildup should be explored, and people should refuse to accept simplistic answers about safety and protection when there is little proof that security technology really does make society safer.